Great Green Transition and Finance - Claudia Kemfert; Dorothea Schäfer; Willi Semmler (Intereconomics)
Abstract European governments are struggling to regain economic strength in the coronavirus pandemic as in many countries the number of new infections seems to gradually subside. Growth rates deep in the red call for a reconstruction programme when the crisis is finally manageable and economic activity can resume. Amidst this, there are again influential groups that claim “this is not the time to insist on strict climate protection goals”. On the contrary, the ongoing COVID-19 crisis has clearly illustrated what climate disasters, often occurring locally, could do to the life of citizens. The reconstruction programme needs to initiate the great green transition. The transformation from a climate-distorting to a climate-protecting economy opens up investment opportunities and points to financing needs comparable with those necessary for the rebuilding of the European economy after World War II. The great green transition is a unique chance to pursue policies for a new and sustainable growth regime.